HUBUNGAN KARAKTER SISWA DENGAN PRESTASI BELAJAR DALAM MATA PELAJARAN PAI DI SMP INSAN KAMIL BOGOR - Siti Nurhasanah; Muhammad Rizal; Ratu Dinny Fauziah; Abdul Kodir (Jurnal Cendekia Ihya, 2023)
This research discusses the relationship between student character and learning achievement in PAI subjects at Insan Kamil Junior High School, Bogor. This research was motivated by the poor performance of Indonesian students, based on the International Student Assessment Programme’s 2018 report, which ranked Indonesia in the bottom 10 out of 79 Southeast Asia countries. This research aims to: (1) determine the state of the student’s character, (2) determine the state of the student’s learning achievement, and (3) determine the relationship between the student’s character and PAI learning achievement at Insan Kamil Bogor Junior High School. The population of this study consisted of only class VII students of Insan Kamil Junior High School Bogor, totaling 147 students. The sampling method and the number of respondents was 105. Data collection methods use observation and documentation. The analysis technique used is simple linear regression analysis. Based on a simple linear regression analysis, we get the equation Ŷ=48.264+2.651X. the results of hypothesis testing (Pearson correlation) show that the student’s character variables have a significant relationship with learning achievement in PAI subjects at Insan Kamil Junior High School Bogor, and the correlation coefficient is 0.476. However, based on the calculation of the coefficient of determination (R2), the adjusted R square value is 0.219. This indicates that student’s character variables collectively have a significant influence on the learning achievement in PAI subjects at Insan Kamil Bogor Junior High School, namely 21.9%. The remaining 78.1% was influenced by other variables not investigated in this research.